The Integration of Religion and Culture to Construct Social Identity Through The Pukul Sapu Ritual in Mamala Village, Moluccas - Flavius Floris Andries (Humaniora, 2018)
The integration of religion and culture to build the discourse of social identity is an interesting issue. For Mamala, a village in the Moluccas, Indonesia, society consists of two embedded identities, namely religion and culture, in the construction of social identities. This research discusses religious and cultural integration in the construction of social identity by means of a flagellation ritual known as pukul sapu. This research applies qualitative methods to analyze qualitative data gathered through observation, in-depth interviews and document reviews. In particular, this research attempts to answer (a) why the pukul sapu ritual is performed by the Mamala community on the seventh day after Iedul Fitri, (b) how the ritual is carried out, (c) what elements are used in the ritual process, and (d) what meaning emerged in connection with the construction of their identity as Muslims and also as a society of customs. The research subjects consisted of a number of religious figures, customary figures, and people who are directed to participate in the review process of the ritual. This study shows that the ritual is regarded as a medium to construct the social identity (religion and culture). The integration of religion and culture in Mamala has proven that the social identity of this society includes religion and culture formed by dialectical processes, namely adaptation, relations, and negotiations between local traditions coupled with the influence of Javanese traditions. This, in fact, describes liquid social identity instead of static movement.